The difference of angles between Down-The-Side Line Shot and Cross Shot of the two-handed backhand stroke in tennis as a basis for skill training - Salah Abdou, H.; Hassanien, A. A. F. (American Journal of Sports Science, 2022)
The purpose of this study was to investigate the difference in angles between a Cross shot and Down-The-Side line shot stroke for the skill of the Tow-Handed backhand in beginning of back swing, end of back swing, ball impact, and end of follow through. There are 9 players in the Top -10 of Association of Tennis professional (ATP) are used two-handed backhand batting Technology, that is 90%. Two-handed backhand grips influence both the strength and the coordination used in the stroke. Sample of subjects Five experienced young boys` tennis players from Sporting club in Alexandria, Egypt. They are participating in national championships. Biomechanics is an essential tool for understanding movement and the adjustments in the stroke of tennis. Methods we are using Simi 3D motion analysis V.9.0.6 Program of Kinematic analysis to data analysis. The results of Man-Whitney nonparametric test for comparing 2 independent groups. Results This study success to show differences in angles between a Cross shot and Down-The-Side line shot stroke for the skill of the Tow-Handed backhand. Conclusion Cross shot stroke for the skill of the Tow-Handed backhand need to more rotation in lower and upper body than Down-The-Side line shot stroke for the skill of the Tow-Handed backhand to hit the ball in cross court successfully. We may need more research to understand more of the differences between a Cross shot and Down-The-Side line shot stroke for the skill of the Tow-Handed backhand from other sides.